Supervision and Assistance in Resolving Problematic Loans at Tangguh Mitra Bersama Cooperative - Perkasa, Ripho Delzy; Rismawati, Lia; Aulia, Rina; Delaila, Ifani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The Solid Partner Cooperative is a people's economic entity that plays a crucial role in supporting the local economy. However, like other financial institutions, cooperatives also face challenges in resolving problematic credits that can affect their stability and operational sustainability. Therefore, this journal adopts a qualitative research approach to analyze the coaching and assistance strategies in handling problematic credits at the Solid Partner Cooperative. The research findings indicate that a deep understanding of cooperative principles, active member involvement in decision-making, transparency and accountability in financial management, and collaboration with other financial institutions or financial experts are key factors in cooperative management coaching. A strong understanding of cooperative principles creates a solid foundation for members and cooperative managers to carry out operational activities and make strategic decisions. Active member involvement in decision-making creates a democratic and inclusive environment, strengthening member trust in the cooperative. Transparency and accountability in financial and operational management form a strong foundation for building trust and integrity among members and other stakeholders. Collaboration with other financial institutions or financial experts is an effective strategy in supporting the resolution of problematic credits. By gaining additional access to financial resources, objective advice and insights, and alternative solutions from parties with extensive knowledge and experience, cooperatives can better address credit issues.